Cardiorenal syndrome in the pediatric population: A systematic review - Subal Kumar Pradhan; Harsha Adnani; Rama Safadi; Keval Yerigeri; Snehamayee Nayak; Rupesh Raina; Rajiv Sinha (Wolters Kluwer Medknow Publications, 2022)
The concept of cardiorenal syndrome (CRS) is derived from the crosstalk between the heart and kidneys in pathological conditions. Despite the rising importance of CRS, there is a paucity of information on the understanding of its pathophysiology and management, increasing both morbidity and mortality for patients. This review summarizes the existing conceptual pathophysiology of different types of CRS and delves into the associated therapeutic modalities with a focus on pediatric cases. Prospective or retrospective observational studies, comparative studies, case reports, case-control, and cross-sectional studies that include pediatric patients with CRS were included in this review. Literature was searched using PubMed, EMBASE, and Google Scholar with keywords including "cardio-renal syndrome, type," "reno-cardio syndrome," "children," "acute kidney injury," and "acute decompensated heart failure" from January 2000 to January 2021. A total of 14 pediatric studies were ultimately included and analyzed, comprising a combined population of 3608 children of which 32% had CRS. Of the 14 studies, 57% were based on type 1 CRS, 14% on types 2 and 3 CRS, and 7% were on types 4 and 5 CRS. The majority of included studies were prospective cohort, although a wide spectrum was observed in terms of patient age, comorbidities, etiologies, and treatment strategies. Commonly observed comorbidities in CRS type 1 were hematologic, oncologic, cardiology-related side effects, muscular dystrophy, and pneumonia/bronchiolitis. CRS, particularly type 1, is prevalent in children and has a significant risk of mortality. The current treatment regimen primarily involves diuretics, extracorporeal fluid removal, and treatment of underlying etiologies and comorbidities.